Class II HLA diabetogenic markers in an Udmurtian population: genotype dependence, the role of DQ trans-heterodimers - Olga Nikolavna Ivanova; Sergey Alexandrovich Prokof'ev; Yana Stanislavovna Zvereva; Tatiana Viktorovna Kovalenko; Andrey Vladimirovich Blinov; Valentina Alexandrovna Peterkova (Сахарный диабет)
Aim. To analyse association of class II HLA genotype (DRB1, DQA1, DQB1) with type 1 diabetes mellitus (DM1) in an Udmurtian population. Materials and methods. The case-control method was applied in the study involving 29 children with DM1 and 97 age-matched healthy subjects. HLAalleles were identified by multiprimer allele-specific PCR. Association with DM1 was evaluated from the OR-odds ratio. Calculations were made usingStatSoft and STATISTICA 6 programs. Results. The occurrence of ?classical? highly predisposing haplotypes in the studied Udmurtian population proved significantly lower than in otherCaucasoid populations (DRB1*04-DQA1*0301-DQB1*0302 - 2,6 vs 8-16% and DRB1*17(03)-DQA*0501-DQB1*0201 - 3,6 vs 6-12,9%)trans-Encoded DQ heterodimers (DQA1*0301-DQB1*0201 and DQA1*0301-DQB1*0302) were shown to play the key role in determining the riskof DM1. They were found in 62,1% of the patients compared with 10,3% of control subjects (OR=14,2; pc=6Ч10-5). Conclusion. Positive DQA1*0301-DQB1*0302 or/and *0201 genotype is the most sensitive predictor of DM1 in the studied Udmurtian population.